Acquisition and presentation system for Energy Management – design and implementation - Lukasz Korus; Andrzej Jablonski (International Journal of Electronics and Telecommunications)
Energy Management (EMS) is understood as the effort to minimize energy consumption in industrial facilities through a continuous improvement approach. Decentralized Control Systems (DCS) concentrated on optimizing energy consumption in small and medium enterprises (SMEs) are still rarely used. The practical application of the continuous improvement approach relies on a Deming-like cycle, utilizing data gathered through Data Acquisition and Presentation Systems. The article addresses the issue of designing and implementing such type of systems as foundation of Energy Management in SMEs.